2002
DOI: 10.1128/jvi.76.21.11133-11138.2002
|View full text |Cite
|
Sign up to set email alerts
|

Implication of the Lymphocyte-Specific Nuclear Body Protein Sp140 in an Innate Response to Human Immunodeficiency Virus Type 1

Abstract: The viral infectivity factor (Vif) of human immunodeficiency virus type 1 (HIV-1) neutralizes an unidentified antiviral pathway that occurs only in nonpermissive (NP) cells. Using a yeast two-hybrid screen of a human lymphocyte cDNA library, we identified several potential Vif partners. One, the nuclear body protein Sp140, was found specifically in all NP cells (n ‫؍‬ 12 cell lines tested; P < 0.001), and HIV-1 infection induced its partial dispersal from nuclear bodies into cytosolic colocalization with Vif. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 57 publications
3
37
0
1
Order By: Relevance
“…This discrepancy was explained when more YFP-Vif appeared to localize to the cytoplasm when immunolocalized with either ␣-Vif or ␣-GFP, which suggests that cytoplasmic Vif is more amenable to immunostaining. Altogether these results demonstrated that a more substantial fraction of Vif localizes to the nucleus than described previously and are consistent with previous findings that show Vif interacts with nuclear proteins Sp140 (43) and ZIN (44).…”
Section: Discussionsupporting
confidence: 82%
“…This discrepancy was explained when more YFP-Vif appeared to localize to the cytoplasm when immunolocalized with either ␣-Vif or ␣-GFP, which suggests that cytoplasmic Vif is more amenable to immunostaining. Altogether these results demonstrated that a more substantial fraction of Vif localizes to the nucleus than described previously and are consistent with previous findings that show Vif interacts with nuclear proteins Sp140 (43) and ZIN (44).…”
Section: Discussionsupporting
confidence: 82%
“…A variety of Vif-interacting host factors have since been identified. These include vimentin (20), Hck (17), sp140 (28), and CEM15 (36). In fact, expression of Hck and CEM15 appeared to be associated with inhibition of viral infectivity in a Vif-dependent manner (17,36).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed a number of cellular factors have been shown to interact with Vif. These include tyrosine kinase Hck (14), an ATP-binding protein, HP68 (45), and lymphocyte-specific nuclear body protein Sp140 (25). However, the biological significance of these cellular factors in relation to their association with Vif is not clear.…”
mentioning
confidence: 99%